(untitled) (Raparin Journal of Humanities (RJH), 2024)
This research under the address of address of (the phenomenon of loss and feminization in a grammatical gender in Kurdish language in Slivanian plain) has given as an example. According this address we will try to declare (show) (what are the signs that can be grammatical gender? And in how many cases they appear? The lacke of the grammatical gender appear in which case of this district? The change in the appear in which case of the same district? In which case of lack ang the change of the grammatical gender appear more? Finally it has been shown that the signs of the lack of feminization of the grammatical gender apperr in some cases. This research consists of two sections. The first section is customized for the gender and the grammar that contain thes subjects: (gender concept, gender kinds, the intent of grammatical gender, the specifics of grammatical gender, the signs like the morpheme of the grammatical gender, the gender and the environment, the gender, lack of and the change, the gender and its shed, the reasons of changing the grammatical gender, the case and the gender). The second section is customized for (the phenomenon of loss and feminization in the grammatical gender in Slivanian plain) in which the lack of gender in the case of (Addition, Indirct, perfect, Continuity, Signal, Structuralism, call) are appeared and the phenomenon of feminization appear of (Addition, Indirct, perfect, Continuity, Signal, Structuralism,call )